Activation of MEK‐ERK‐c‐MYC signaling pathway promotes splenic M2-like macrophage polarization to inhibit PHcH-liver cirrhosis - Guihu, Wang; Wei, Dong; Hailong, Zhang; Chongyu, Zhang; Jin, Sun; Mengchen, Zhu; Jian, Zhang; Rui, Zhou; Song, Ren; Chen, Zhang; Xi, Liu (Frontiers in Immunology, 2024)
IntroductionPortal hypertension combined with hypersplenism (PHcH) is the main cause of hypocytosis and esophagogastric variceal hemorrhage in patients with liver cirrhosis. Activated macrophages that destroy excess blood cells are the main cause of hypersplenism, but the activating pathway is not very clear. This study aims to investigate the activation types of splenic macrophages and their activation mechanisms, to provide experimental evidence for the biological treatment of splenomegaly, and to find a strategy to improve liver fibrosis and inflammation by intervening in splenic immune cells. This study revealed the occurrence of M2-like polarization of macrophages and upregulation of c-Myc gene expression in the PH spleen.MethodsRNAseq, protein chip, western blot, and chip-seq were performed on macrophages and the in vitro MEK inhibitor rafametinib was used. Carbon tetrachloride and thioacetamide induced mouse cirrhosis models were separately constructed.Resultsc-Myc gene knockout in splenic macrophages reduced M2-like polarization and exacerbated liver fibrosis inflammation. c-Myc activated the MAPK signaling pathway and upregulated the expression of IL-4 and M2-like related genes in PH hypersplenism through the MEK-ERK-c-Myc axis. In addition, the c-Myc gene exerted anti-inflammatory effects by upregulating IL-4-mediated signal transduction to promote M2-like differentiation and anti-inflammatory cytokine secretion.ConclusionsActivation of MEK‐ERK‐c‐MYC signaling pathway promotes splenic M2-like macrophage polarization to inhibit PHcH-liver cirrhosis. Therefore, the induction of macrophage depolarization might represent a new therapeutic approach in the cure of PH hypersplenism, making c-Myc a potential candidate for macrophage polarization therapy.